Min (Max)-CS Modules - Majeed, R . N.; Hadi, I. M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we give a comprehensive study of min (max)-CS modules such as a closed submodule of min-CS module is min-CS. Amongst other results we show that a direct summand of min (max)-CS module is min (max)-CS module. One of interested theorems in this paper is, if R is a nonsingular ring then R is a max-CS ring if and only if R is a min-CS ring.